Indirect Comparison Showed Survival Benefit from Adjuvant Chemoradiotherapy in Completely Resected Gastric Cancer with D2 Lymphadenectomy - Qiong Yang; Ying Wei; Yan-Xian Chen; Si-Wei Zhou; Zhi-Min Jiang; De-Rong Xie (Gastroenterology Research and Practice)
Background. Little data on directly comparing chemoradiotherapy with observation has yet been published in the setting of adjuvant therapy for resected gastric cancer who underwent D2 lymphadenectomy. The present indirect comparison aims to provide more evidence on comparing the two approaches. Methods. We conducted a systematic review of randomized controlled trials, extracted time-to-event data using Tierney methods (when not reported), and performed indirect comparison to obtain the relative hazards of adjuvant chemoradiotherapy to observation on overall and disease-free survival. Results. seven randomized controlled trials were identified. Three trials compared adjuvant chemoradiotherapy with adjuvant chemotherapy, and 4 trials compared adjuvant chemotherapy with observation. Using indirect comparison, the relative hazards of adjuvant chemoradiotherapy to observation were 0.43 (95% CI: 0.33–0.55) in disease-free survival and 0.52 (95% CI: 0.38–0.71) in overall survival for completely resected gastric cancer with D2 lymphadenectomy. Conclusions. Postoperative chemoradiotherapy can prolong survival and decrease recurrence in patients with resected gastric cancer who underwent D2 gastrectomy. Molecular biomarker might be a promising direction in the prediction of clinical outcome to postoperative chemoradiotherapy, which warranted further study.